Recent Advances and Future Trends in Pavement Engineering - De Maeijer, Patricia Kara (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue "Recent Advances and Future Trends in Pavement Engineering" was proposed and organized to present recent developments in the field of innovative pavement materials and engineering. The 12 articles and state-of-the-art reviews highlighted in this editorial are related to different aspects of pavement engineering, from recycled asphalt pavements to alkali-activated materials, from hot mix asphalt concrete to porous asphalt concrete, from interface bonding to modal analysis, and from destructive testing to non-destructive pavement monitoring by using fiber optics sensors. This Special Issue partly provides an overview of current innovative pavement engineering ideas that have the potential to be implemented in industry in the future, covering some recent developments.